ALAT PENGUKUR TEGANGAN DAN ARUS MENGGUNAKAN ARDUINO MEGA 2560 BERBASIS PESAN SINGKAT (SMS) - Beni Frianto; Yulisman Yulisman; Budi Santosa (Ensiklopedia of Journal, 2020)
Many distribution transformers at Rayon Baso 197 units scattered in the work area of Rayon Baso in direct measurements one by one to the field at 17:00 to 22:00 with limited time and done at night have a high enough risk value to measure load the transformer thoroughly. To overcome these obstacles then made a tool called the Voltage And Flow Meter Using Arduino Mega 2560 Based Short Message (SMS) which will be installed in substations - distribution substations. This tool will measure the voltage and current in the distribution substation by sending the voltage and current information read by the tool through Short Message communication. It is hoped that this tool will help monitor the burden of the distribution transformer and reduce the high risk value of Rayon Baso.